2014
DOI: 10.1097/cmr.0000000000000037
|View full text |Cite
|
Sign up to set email alerts
|

Palmar and plantar melanomas differ for sex prevalence and tumor thickness but not for dermoscopic patterns

Abstract: The specific anatomy of the glabrous skin, characterized by marked orthokeratosis and the presence of furrows and ridges, results in peculiar dermoscopic patterns of acral melanocytic lesions. Most frequently, acral nevi are typified by a parallel furrow pattern and acral melanoma (AM) by a parallel ridge pattern (PRP). Although the dermoscopic patterns of AM have been extensively investigated, little attention has been paid to site-related differences between palmar and plantar AM. The current study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
2
14
1
1
Order By: Relevance
“…Lastly, in situ lesions were significantly more prevalent in fingernails than toenails, which is likely due to easier detection. A similar report has been published in the volar skin region . These clinical observations may shed light on the elusive pathogenesis of NAM, but should be confirmed by further studies.…”
Section: Patient Data and Topographical Distribution Of Nail Apparatusupporting
confidence: 82%
See 1 more Smart Citation
“…Lastly, in situ lesions were significantly more prevalent in fingernails than toenails, which is likely due to easier detection. A similar report has been published in the volar skin region . These clinical observations may shed light on the elusive pathogenesis of NAM, but should be confirmed by further studies.…”
Section: Patient Data and Topographical Distribution Of Nail Apparatusupporting
confidence: 82%
“…A similar report has been published in the volar skin region. 10 These clinical observations may shed light on the elusive pathogenesis of NAM, but should be confirmed by further studies.…”
mentioning
confidence: 80%
“…9,14-28 However, it has recently been shown that approximately one-third of AMs do not display a PRP, thus rendering their accurate diagnosis more difficult. 29 Some additional features, such as irregular diffuse pigmentation and other nonsite-specific melanoma criteria, have also been reported to characterize AM. [15][16][17][18]25,27 The aim of the present study was to develop and validate a multivariable dermoscopic prediction model for the differentiation between early AMs and acral naevi.…”
mentioning
confidence: 99%
“…In acral pigmented lesions, dermoscopy enhances melanoma recognition by highlighting the accentuation of the pigmentation on the skin ridges [parallel ridge pattern (PRP), in contrast to the parallel furrow pattern (PFP) of acral naevi] . However, it has recently been shown that approximately one‐third of AMs do not display a PRP, thus rendering their accurate diagnosis more difficult . Some additional features, such as irregular diffuse pigmentation and other nonsite‐specific melanoma criteria, have also been reported to characterize AM …”
mentioning
confidence: 99%
“…The role of sun exposure is not relevant for either the palm or sole; however, the palm is less weight bearing and is often exposed to more recurrent trauma. 7 Even though Lallas et al 8 found that palmar and plantar melanomas show similar dermoscopic features, there could be biological factors, such as trauma, mechanical stress or the lymphatic system, that might determine more aggressive clinical courses of melanomas arising on the palm. Follow-up of six patients with invasive palmar melanoma indicated regional or distant metastasis within 1 year.…”
mentioning
confidence: 99%